A new species of Dixonius (Squamata: Gekkonidae) from Vientiane Capital, Laos - Nguyen, Thuong Huyen; Luu, Vinh Quang; Sitthivong, Saly; Ngo, Hanh Thi; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2021)
A new species of the gekkonid genus Dixonius is described from Huaysorn-Huaysua village, Nasaithong District, Vientiane Capital, Laos. The new species can be distinguished from all other species by a combination of the following characters: maximum SVL 47.1 mm; 19–21 longitudinal rows of dorsal tubercles at midbody; 23–26 longitudinal rows of ventrals across the abdomen; 7 or 8 supralabials, 6 in mid-orbital position; 5 or 6 infralabials; 5 or 6 precloacal pores in males, femoral pores lacking; precloacal and femoral pores absent in females; a canthal stripe running from rostrum through the eye and terminating at back of head; dorsum brown with irregular dark marks. In phylogenetic analyses, the species is recovered as the sister taxon to D. siamensis, which occurs in Laos, Thailand, and Vietnam. Genetically, the two species are approximately 9.4% divergent from each other based on the complete mitochondrial ND2 gene with six partial or complete adjacent tRNAs. It is the 12th species known in the genus Dixonius and the second Dixonius species described from Laos.